2014
DOI: 10.1155/2014/219437
|View full text |Cite
|
Sign up to set email alerts
|

Eventually Periodic Solutions of a Max-Type Difference Equation

Abstract: We study the following max-type difference equation x n = max⁡{A n/x n−r, x n−k}, n = 1,2,…, where {A n}n=1 +∞ is a periodic sequence with period p and k, r ∈ {1,2,…} with gcd(k, r) = 1 and k ≠ r, and the initial conditions x 1−d, x 2−d,…, x 0 are real numbers with d = max⁡{r, k}. We show that if p = 1 (or p ≥ 2 and k is odd), then every well-defined solution of this equation is eventually periodic with period k, which generalizes the results of (Elsayed and Stevic´ (2009), Iričanin and Elsayed (2010), Qin et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Recently, Xiao and Shi [24] studied equation 5, when k � 1, and the result that every well-defined solution is eventually periodic with period 2 is obtained. Because of the necessity for some techniques, in 2014, Sun et al [25] considered the following max-type equation that extends the form of equation (5):…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xiao and Shi [24] studied equation 5, when k � 1, and the result that every well-defined solution is eventually periodic with period 2 is obtained. Because of the necessity for some techniques, in 2014, Sun et al [25] considered the following max-type equation that extends the form of equation (5):…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, scholars have studied many theories and applications of the max-type difference equation in recent years. Since periodical research of differential equation theory has been very mature and perfect, some scholars try to investigate the periodicity of difference equation with the theory of differential equation (see, e.g., [11][12][13][14][15][16][17] and the reference therein).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that every positive solution of (1.7) is eventually periodic with period sT for some T ∈ N if f ji j satisfy some conditions. For some results of some properties of many max-type difference equations and systems, such as eventual periodicity, the boundedness character, and attractivity, see, e.g., [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and the related references therein.…”
Section: Introductionmentioning
confidence: 99%